The development of fish epithelial cell lines and primary cultures as diagnostic tools in environmental risk assessment - Dowling, Kevin J. (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2000)
The objective of the this study was to attempt and develop fish epithelial cellular markers as diagnostic tools for effects assessment in ecotoxicolgy using established cell lines and primary cultures. As a target group in the environment teleost fish were selected.
Keywords: Biochemistry, Ph.D; Ph.D. Trinity College Dublin